2018
DOI: 10.1002/jcb.28102
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 regulates monocyte activation through AMPK‐mTOR nexus under high‐glucose and dyslipidemic conditions

Abstract: The vicious cycle between hyperinsulinemia and insulin resistance results in the progression of atherosclerosis in the vessel wall. The complex interaction between hyperglycemia and lipoprotein abnormalities promotes the development of atherogenesis. In the early phase of atherosclerosis, macrophage‐derived foam cells play an important role in vascular remodeling. Mechanistic target of rapamycin (mTOR) signaling pathway has been identified to play an essential role in the initiation, progression, and complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…In this perspective, two molecular pathways are related with anti-inflammatory response together with the metabolic reprogramming in myeloid cells. On the one hand AMP-activated protein kinase (AMPK), a kinase energetic sensor, induces the oxidative pathway in immune cells, promoting an anti-inflammatory profile in macrophages and lymphocytes, chronically 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, two molecular pathways are related with anti-inflammatory response together with the metabolic reprogramming in myeloid cells. On the one hand AMP-activated protein kinase (AMPK), a kinase energetic sensor, induces the oxidative pathway in immune cells, promoting an anti-inflammatory profile in macrophages and lymphocytes, chronically 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SESN2-knockdown mice had higher plasma pro-inflammatory cytokine levels and increased monocyte recruitment to the vascular endothelium by secreting monocyte adhesion molecules [intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1] through inhibiting the AMPK signaling pathway and downregulating the ER stress pathway, which contributed to atherosclerosis initiation (32). Similarly, another study reported that SESN2 regulated monocyte polarization and adhesion to endothelial cells and decreased inflammatory responses by regulating the AMPK–mTOR nexus under high-glucose and dyslipidemic conditions (95). Moreover, in a sepsis mouse model and in septic shock patients, SESN2 levels were increased and peaked at 48 h in blood monocytes, and SESN2 protected organisms against inflammatory responses and septic shock, which were associated with decreased serum concentrations of IL-1β and IL-18 (12).…”
Section: Sesn2 and Immune Cellsmentioning
confidence: 92%
“…The AMPK and mTOR signaling pathways were reported to play an essential role in the initiation and progression of atherosclerosis [ 29 , 30 ], and sestrin2 was shown to modulate mTOR activity, thereby regulating glucose and lipid metabolism [ 31 , 32 ]. Sundararajan et al reported that high-glucose and oxidized LDL treatment mediated the production of proinflammatory cytokine (M1) with a concomitant decrease in anti-inflammatory cytokine (M2) levels in macrophages [ 33 ]. M2 macrophages promote the secretion of IL-10, transforming growth factor-β (TGF-β), and extracellular matrix to protect vessels from atherosclerosis, whereas M1 macrophages secrete matrix metalloproteinases (MMPs) and proinflammatory factors such as TNF-α, IL-6, and IL-1β [ 34 ].…”
Section: Physiopathological Mechanisms Of Sestrin2mentioning
confidence: 99%
“…M2 macrophages promote the secretion of IL-10, transforming growth factor-β (TGF-β), and extracellular matrix to protect vessels from atherosclerosis, whereas M1 macrophages secrete matrix metalloproteinases (MMPs) and proinflammatory factors such as TNF-α, IL-6, and IL-1β [ 34 ]. Glucose and oxidized LDL increased mTOR activation with a marked reduction in AMPK and sestrin2 expression and increased foam cell formation and monocyte adhesion to endothelial cells [ 33 ]. In addition, the overexpression of sestrin2 regulated the polarization of macrophages toward anti-inflammatory M2, while the knockdown of sestrin2 directed the polarization toward proinflammatory M1 [ 33 ].…”
Section: Physiopathological Mechanisms Of Sestrin2mentioning
confidence: 99%
See 1 more Smart Citation